Revitalizing Local Traditions through Digital Transformation as a Strategy for Building Mataraman Cultural Resilience - Muhammad Hanif; Soebijantoro; Endang Sri Maruti (Lembaga Bale Literasi, 2026)
This study aims to describe the forms of revitalization of local cultural traditions through digital transformation and to formulate strategies for strengthening the cultural resilience of the Mataraman culture in the Pawitandirogo region. The study employs an ethnographic approach, positioning the community as the primary subject in understanding the meanings, values, cultural practices, and processes of adaptation to the development of digital technology. Data collection was conducted through participatory observation, in-depth interviews, focus group discussions (FGDs), documentation, and the study of digital artifacts related to the community’s cultural practices. Research informants were selected through purposive sampling, including traditional leaders, cultural figures, artists, youth, educators, cultural community managers, and local government officials. Data analysis was conducted thematically through the stages of data reduction, data presentation, drawing conclusions, and triangulation of sources, techniques, and time to ensure the credibility of the findings. The research results provide a comprehensive description of the local cultural revitalization practices emerging within the community, the ways in which digital transformation is utilized in the preservation of Mataraman culture, and collaborative strategies involving the public, cultural communities, educational institutions, and local governments to strengthen the resilience of local culture. The research findings are expected to serve as the basis for the development of adaptive, participatory, and sustainable cultural preservation policies and programs so that Mataraman’s cultural identity remains preserved amid the dynamics of a digital society.